UNDERSTANDING THE ROLE OF HOME GARDENS IN HOUSEHOLD FOOD SUPPLY IN TIMES OF SHOCKS AND UNCERTAINTY: EVIDENCE FROM COVID-19 LOCKDOWN IN NIGERIA (American International Journal of Agricultural Studies, 2025)
Home gardening has continued to gain increased interest among researchers because of its role in promoting household food security and strengthening local agrifood systems, particularly in developing countries like Nigeria. In times of shocks like the COVID-19 pandemic, which severely disrupted food supply chains, it offers significant potential to drive sustainable household food supply. However, its potential to fully support household food supply in Nigeria remains underutilized. This study analyzes the role of home gardens in food supply among households during the COVID-19 lockdown, using cross-sectional data from 140 university staff members randomly selected. The data were collected via an online survey during the COVID-19 lockdown and analyzed using a probit model. The result shows that most respondents owned a home garden. However, only 52 percent of the home gardeners obtained food from the garden during the COVID-19 lockdown. Socio-demographic characteristics such as gender and age were inversely related to ownership of a home garden, while household size, house location and education showed a positive and significant relationship. The food crops grown in the home gardens were mainly vegetables, cassava (Manihot esculenta) and maize (Zea mays). The primary reason for owning a home garden was the access to organic food and vegetables.  The findings of this study suggest that home gardens offer the potential to sustain household food supply in times of food shocks and uncertainty.JEL Classification Codes: Q18, Q56, I31, O15, R11.